Coral smuggling (factors, effects, and mechanisms to combat it) - Rahma KERRAS; Feriha MOHAMED KARIM (Social Sciences Journal, 1970)
This present study is aiming atcloselyidentifying the subject of sumggling of coralsthis has beenpossible through rhéprésentation of différent concepts of smuggling, also. The vocable of corrals,and to highlight the main factors pushing the individual to adopt this criminal behavoir, and whatfollows as different harmful consequences. Finally, this study is deoling with different ways ofcombating this phenomenon, either from algerian internal perspective, or from external perspectivethrough Arab cooperation to eliminate partially this phenomenon